2016
DOI: 10.7567/jjap.55.05fl03
|View full text |Cite
|
Sign up to set email alerts
|

Low-ohmic-contact-resistance V-based electrode for n-type AlGaN with high AlN molar fraction

Abstract: We investigated a V-based electrode for the realization of low ohmic-contact resistivity in n-type AlGaN with a high AlN molar fraction characterized by the circular transmission line model. The contact resistivity of n-type Al0.62Ga0.38N prepared using the V/Al/Ni/Au electrode reached 1.13 × 10−6 Ω cm2. Using this electrode, we also demonstrated the fabrication of UV light-emitting diodes (LEDs) with an emission wavelength of approximately 300 nm. An operating voltage of LED prepared using a V/Al/Ni/Au electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…In addition, Ti‐based electrodes have high ρ c to n‐type AlGaN with AlN molar fractions above 0.6 . We reported that V/Al/Ni/Au electrode realized low contact resistivity (∼10 −6 Ωcm 2 ) with n‐type AlGaN with AlN molar fraction of 0.62 . However, we confirmed contact resistivity for AlGaN with AlN molar fraction of 0.7 rapidly increased to 10 −3 Ωcm 2 order.…”
Section: Introductionmentioning
confidence: 45%
“…In addition, Ti‐based electrodes have high ρ c to n‐type AlGaN with AlN molar fractions above 0.6 . We reported that V/Al/Ni/Au electrode realized low contact resistivity (∼10 −6 Ωcm 2 ) with n‐type AlGaN with AlN molar fraction of 0.62 . However, we confirmed contact resistivity for AlGaN with AlN molar fraction of 0.7 rapidly increased to 10 −3 Ωcm 2 order.…”
Section: Introductionmentioning
confidence: 45%
“…To reduce the waste EL on this mechanism, an n-reflective contact was investigated [40]. The sheet resistance of the n-contact on Al x Ga 1−x N (x > 50%) was recorded to be around 10 −4 Ωcm 2 [122] using vanadium. The carrier concentration of the n-AlGaN layer and the electron mobility were reported [123].…”
Section: Interdigital Reflective N-contactmentioning
confidence: 99%
“…Indeed, it was shown that using the traditional metal contact schemes of Ti/ Al/Ti/Au, one can form good Ohmic contacts to n-AlGaN only up to about 20% AlN mole fraction [99]. Other workers have demonstrated that vanadium-based contacts can form good Ohmic contacts to n-GaN [100,101] and also to n-AlGaN [102][103][104].…”
Section: Device Fabricationmentioning
confidence: 99%